PENGARUH COMPUTER ANXIETYTERHADAP KEAHLIAN KARYAWAN DALAM MENGGUNAKAN KOMPUTER - Arlin Effendy; Mi Mitha Dwi Restuti (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2010)
Computer application technology is used by the company to supported the company’s daily operation, to got efficiency and effectiveness on the operation, and to got profit in long term. For some people, they had an anxiety with the growth of the computer’s technology. The purpose of this study was to find the empirical evidence, whether computer anxiety had an effect on computer proficiency or not. Computer anxiety is tendency of someone when she/he got a problem, anxious or afraid in using computer technology. This study used Computer Anxiety Rating Scale (CARS) wich developed by Heissen et. al and Computer Self-Efficacy Scale (CSE)that developed by Murphy et. al. The data findings indicated that computer anxiety had negatif correlation with computer proficiency. It meant that if the employee had computer anxiety, his/her computer proficiency is indicated as low. This finding was consistent with the similar research conducted by Sudaryono and Astuti (2005). Keywords: computer anxiety, computer proficiency